The effects of fermented okara, Glycine max, on Growth performance of tilapia, Oreochromis sp. - Nurfarah Wahida Abd Rahim (2016)
The purpose of this study is to analyze the nutritional profile and microbiological of fermented Okara, Glycine max. The raw Okara was mix with molasses and fermented for 35 days under room temperature. The fermented sample was analyze for proximate (crude protein, crude fat, crude fiber, ash, energy and moisture content) and microbial analyses (total plate count, total yeast count, total lactic acid bacteria count and total mould count) at 7 days interval throughout fermentation. The fermented Okara was then feed ti tilapia fingerlings Oreochromis sp.to study its effect on the growth performance. The fermented Okara showed highest crude protein (35%), crude fat (1%) and ash (5.8%) at 0 day of fermentation. Meanwhile, crude fiber showed 12.2% and energy, 263.7% at first day of fermentation. Majority of the microbial loads exhibited inconsistent trend during fermentation. The TPC showed an increase of microbial load from 6.83±0.19 (0 day) to 7.03±0.04 (14 day) before reduced to 6.06±0.02 log CFU/ml at the end of fermentation. The fermented Okara was then compared to commercial pellet as control treatment in the experiment. The growth performance of tilapia fingerlings fed with fermented Okara showing positive results even with little improvement on the weight gain with 10.83±6.8O on the initial weight increased to 41.00±22.37 compared with fingerling fed with commercial weight which increased until 76.27±10.60 from 21.33±4.44 gram. The specific growth rate of the fingerlings fed with Okara showed slightly higher percent (4.33±0.08) than fingerlings fed with commercial pellet (4.27±O.27). The feed conversion ratio of the fermented Okara showed slightly better value with 2.25±0.08 compared to commercial pellet with 2.32±0.27 percent. Hence, it can be concluded that fermented Okara has potential value to be an alternative protein source to the aquaculture industry.